(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
In recent years, the investment climate in Uzbekistan has improved significantly. Investment legislation adopted by the government, tax incentives, and free economic zones have served to attract both foreign and domestic investors. In addition, the country’s geostrategic location and the development of energy and transport infrastructure are considered important factors stimulating investment. However, the presence of legal guarantee issues and bureaucratic barriers in certain sectors continues to affect investment activity. Therefore, the continuous optimization of investment policy and the creation of competitive conditions are essential for accelerating Uzbekistan’s economic growth